The perceptions and experience of male farm workers of the effects of a transpersonal social work intervention in addressing domestic violence - Brophy, Fiona C. (Stellenbosch : University of Stellenbosch, 2010)
Thesis (M Social Work)--University of Stellenbosch, 2010.